The fabrication and characterization of magnetron sputtered Ni50Mn37In13 ferromagnetic shape memory thin films. - Song, Yu. (2012)
In recent years, ferromagnetic shape memory alloys have drawn an increasing scientific attention due to their large magnetic-field-induced strains and the potential of using these materials as actuators and sensors. Previous findings on NiMnIn ferromagnetic shape memory alloys (SMA) bulk showed a specific martensitic transformation from a ferromagnetic parent phase to an antiferromagnetic martensite phase. In our research, we successfully fabricated the Ni50Mn37In13 thin film on Si (100) substrate by sputtering method which showed a ferromagnetic shape memory effect as in the bulk materials. During the fabrication process, different growing condition such as deposition temperatures, argon pressures, powers, and target-substrate distances by magnetron sputtering were used and the best Ni50Mn37In13 thin film growing condition was investigated. The characterization of Ni50Mn37In13 thin film was achieved by using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Energy Dispersive X-Ray Spectroscopy (EDS), X-ray Diffraction (XRD) and Physical Properties Measurement System (PPMS).